Pediatric Cholestatic Liver Disease: Review of Bile Acid Metabolism and Discussion of Current and Emerging Therapies - Kriegermeier, Alyssa; Green, Richard (Frontiers in Medicine, 2020)
Cholestatic liver diseases are a significant cause of morbidity and mortality and the leading indication for pediatric liver transplant. These include diseases such as biliary atresia, Alagille syndrome, progressive intrahepatic cholestasis entities, ductal plate abnormalities including Caroli syndrome and congenital hepatic fibrosis, primary sclerosing cholangitis, bile acid synthesis defects, and certain metabolic disease. Medical management of these patients typically includes supportive care for complications of chronic cholestasis including malnutrition, pruritus and portal hypertension. However, there are limited effective interventions to prevent progressive liver damage in these diseases, leaving clinicians to ultimately rely on liver transplantation in many cases. Agents such as ursodeoxycholic acid, bile acid sequestrants, and rifampicin have been mainstays of treatment for years with the understanding that they may decrease or alter the composition of the bile acid pool, though clinical response to these medications is frequently insufficient and their effects on disease progression remain limited. Recently, animal and human studies have identified potential new therapeutic targets which may disrupt the enterohepatic circulation of bile acids, alter the expression of bile acid transporters or decrease the production of bile acids. In this article, we will review bile formation, bile acid signaling, and the relevance for current and newer therapies for pediatric cholestasis. We will also highlight further areas of potential targets for medical intervention for pediatric cholestatic liver diseases.